DEXiTree: A program for pretty drawing of trees - Bohanec, Marko (IS'07: Proceedings of the International Multiconference Information Society, 2007)
This paper presents DEXiTree, a computer program for drawing trees. In principle, DEXiTree is aimed at making nice drawings of attribute trees made by DEXi, a computer program for qualitative multi-attribute decision modelling. Apart from that, DEXiTree is quite a general and powerful tree-drawing program that implements four different tree-drawing algorithms (called Distribute, Align, Walker, and QP), draws trees in four different directions (top-down, left-right, bottom-up and right-left) and provides an extensive set of parameters for controlling the appearance of trees and their components. DEXiTree’s functionality includes loading a decision model from a DEXi file, interactively designing the tree layout, saving and loading the layout using an XML format, and rendering the drawing in two graphic formats: vector and raster.